Clinical Outcomes at One-year Follow-up for Patients With Surgical Site Infection After Spinal Fusion. Issue 15 (1st August 2022) - Karamian, Brian A.; Mao, Jennifer; Toci, Gregory R.; Lambrechts, Mark J.; Canseco, Jose A.; Qureshi, Mahir A.; Silveri, Olivia; Minetos, Paul D.; Jallo, Jack I.; Prasad, Srinivas; Heller, Joshua E.; Sharan, Ashwini D.; et al.
Abstract : Study Design: Retrospective case-control study. Objective: To compare health-related quality of life outcomes at one-year follow-up between patients who did and did not develop surgical site infection (SSI) after thoracolumbar spinal fusion. Summary of Background Data: SSI is among the most common healthcare-associated complications. As healthcare systems increasingly emphasize the value of delivered care, there is an increased need to understand the clinical impact of SSIs. Materials and Methods: A retrospective 3:1 (control:SSI) propensity-matched case-control study was conducted for adult patients who underwent thoracolumbar fusion from March 2014 to January 2020 at a single academic institution. Exclusion criteria included less than 18 years of age, incomplete preoperative and one-year postoperative patient-reported outcome measures, and revision surgery. Continuous and categorical data were compared via independent t tests and χ 2 tests, respectively. Intragroup analysis was performed using paired t tests. Regression analysis for ∆ patient-reported outcome measures (postoperative minus preoperative scores) controlled for demographics. The α was set at 0.05. Results: A total of 140 patients (105 control, 35 SSI) were included in final analysis. The infections group had a higher rate of readmission (100% vs. 0.95%, P <0.001) and revision surgery (28.6% vs. 12.4%, P =0.048). Both groups improved significantly in Physical Component Score (control: P =0.013, SSI: P =0.039), Oswestry Disability Index (control: P <0.001, SSI: P =0.001), Visual Analog Scale (VAS) Back (both, P <0.001), and VAS Leg (control: P <0.001, SSI: P =0.030). Only the control group improved in Mental Component Score ( P <0.001 vs. SSI: P =0.228), but history of a SSI did not affect one-year improvement in ∆MCS-12 ( P =0.455) on regression analysis. VAS Leg improved significantly less in the infection group (−1.87 vs. −3.59, P =0.039), which was not significant after regression analysis (β=1.75, P =0.050). Conclusion: Development of SSI after thoracolumbar fusion resulted in increased revision rates but did not influence patient improvement in one-year pain, functional disability, or physical and mental health status.